Telaah Kasus Sengketa Hasil Pilkada Depok Dalam Perspektif Yuridis - Ni'matul Huda (Fakultas Hukum Universitas Islam Indonesia, 2005)
Cases related to the Election of the Head of Regent in Depok bestows a significant lessonfor allofus,particularly to the District Election Committee. The involvement of law and politics are very dominant on the Election. Consequently, the District Election Committee and Commission of District Watch are demanded tobe professional, because if there is a dispute in the future the credibility of the Commission of District Election isgoing to be that is at stake.